The girl from Summer Hill : a Summer Hill novel - Deveraux, Jude (Deveraux, Jude. Summer Hill novel., 2016)
"The first book of a new contemporary romance series set in the mountains of Virginia. Sparks fly as fiery Casey Reddick and brooding Hollywood actor Tate Landers clash in the Virginia summer heat. A chef who puts her career first and her love life second, Casey doesn't see what every girl in town is swooning over. She made up her mind the moment she met Tate--he's gorgeous, but stuck-up, nothing like his ex-brother-in-law, Devlin who's playing the Wickham to Tate's Darcy in local production of Pride & Prejudice. Casey makes the perfect Elizabeth Bennett--how could she be star-struck when she's heard Devlin's damning stories about Tate? As they rehearse together, however, Casey finds herself attracted to Tate--he's much more down-to-earth than she expected and any physical contact between the two of them literally gives her a tingling, electric shock. As opening night draws near, Casey has some difficult decisions to make. Whom should she believe? The seemingly sincere, slighted Devlin or Tate, whose rough, arrogant exterior may only be skin deep. She's come to love that jolt she gets when they touch--but will she get burned?"--